White bird : a Wonder story [videorecording (DVD)] - Bomback, Mark; Glaser, Ariella, 2005-; Schwerdt, Orlando; Gheisar, Bryce, 2004-; Anderson, Gillian, 1968-; Mirren, Helen; Königswieser, Matthias, 1981-; Newman, Thomas, 1955-; Palacio, R. J. (Lionsgate, 2024)
Struggling to fit in at his new school after being expelled for his treatment of Auggie Pullman, Julian is visited by his grandmother and is transformed by the compassionate and heroic story of her attempts to escape Nazi-occupied France during WWII.